Social determinants of health associated with the development of sepsis in adults: a scoping review protocol. Issue 10 (27th October 2020) - Machon, Christina; Sheikh, Fatima; Fox-Robichaud, Alison
Abstract : Introduction: Sepsis, the life-threatening immune response to infection, affects millions of people annually. Understanding of the factors associated with the development of sepsis is crucial for improving population health and public health efforts; in particular, literature exploring the relationship between sepsis and social determinants of health is lacking. This review seeks to establish and amalgamate existing evidence of the relationships between sepsis and the following social determinants: frailty, registration with a family physician, mental illness, alcohol abuse, social support levels, smoking status, illicit drug use disorders, socioeconomic status, gender and race/ethnicity. Methods and analysis: This study will analyse qualitative and quantitative studies using standard processes. The selected social determinants of health and their potential link to adult sepsis will be analysed separately under distinct headings. Findings will be consolidated in a final discussion. PubMed and Medline will be searched for articles published between 1970 and 2020 using search strings combining 'sepsis' and other variations, such as 'septicaemia' with each social determinant of interest. 'Sepsis' and at least one social determinant of interest must be present in a study's title for inclusion in the review; the results of the initial search will be filtered based on predetermined inclusion and exclusion criteria. Evidence from this scoping review will provide information on the impact of social determinants of health on the risk of developing adult sepsis, which can inform clinicians of the various risk factors to consider when admitting patients. Ethics and dissemination: Approval from a research ethics board is not needed for this amalgamation of information from studies for which the primary investigators have obtained their own, respective ethics board approval. Once completed, the review will be submitted for publication in a peer-reviewed journal, and findings will be presented in local and national forums.